Music Right from the Start: Theory and Practice of Early Childhood Music Education - Dartsch, Michael; Economidou Stavrou, Natassa; Piispanen, Ulla (Bonn Vdm Verlag European Music School Union, 2022)
In the framework of the AEC – Strengthening Music in Society project, co-funded by Creative Europe, the Working Group on Early Childhood Music Education developed and published this handbook.With this publication, the Working Group members want to offer some ideas from literature and their own experience as early childhood music practitioners and researchers, with the hope that it will stimulate interest in the magical world of music in the early years. The book shall help to establish music lessons with young children all over Europe. For teachers who have to earn their living with their profession, this can even open up a new facet in their professional portfolio.
Keywords: Music education